Cooking skills and food insecurity - Diego Monteza-Quiroz; Andres Silva; Maria Isabel Sactic (PLoS ONE, 2025)
Cooking skills play a relevant role in food security, which encompasses the availability, accessibility, utilization, and stability of food. While previous discussions have mainly focused on accessibility, particularly economic access through food prices and income, this article explores the dimension of food utilization by analyzing the relation between food insecurity and cooking-related variables. We conducted a survey of 106 low-income households in an urban area of Santiago, Chile. Food insecurity was measured using the Food Insecurity Experience Scale (FIES) developed by the FAO. Using principal component analysis, we constructed two indexes reflecting subjective perceptions of cooking skills. We then applied probit models to examine how both subjective and objective cooking skills variables are associated with the probability of experiencing food insecurity. Results show that individuals who can prepare six to ten egg preparations have an 8.4 percentage point lower prevalence of experiencing food insecurity, while those who can prepare more than ten such preparations show a 30.5 percentage point lower prevalence compared to those who can prepare five or fewer. Moreover, our results found a positive prevalence between negative subjective perceptions and food insecurity of 8.8 percentage point. For the first time, this study jointly examines subjective perceptions and self-reported objective measures of cooking skills in relation to food insecurity. We hope this work contributes to expanding the food insecurity discussion beyond economic access and supports the design of food security policies focused on improving cooking aspects.